The Meaning of Employer Branding for Gen Z: A Phenomenological Study of Expectations and Values in Choosing a Workplace - Hardiningrum, Iing Sri; Harianto, Kukuh (RISK : Jurnal Riset Bisnis dan Ekonomi, 2024)
This study aims to explore the meaning of employer branding from the perspective of Generation Z in choosing a workplace. The phenomenon of increasing dominance of Gen Z in the Indonesian job market poses new challenges for companies in developing employer branding strategies that are not only visually appealing but also value-relevant. Using a qualitative approach of interpretive phenomenology, this study explores the subjective experiences of five Gen Z participants aged 21–27 who are in the job search or transition phase. Data collection techniques were carried out through in-depth semi-structured interviews, visual documentation, and observations of digital activities related to job search. Data analysis was carried out using a thematic approach through the stages of reduction, categorization, and interpretation.The results of the study revealed five main themes: (1) the importance of personal value fit with the organization, (2) employer branding as a reflection of social and professional identity, (3) sensitivity to authenticity versus image in branding, (4) employer branding as a determinant of career decisions, and (5) the need for an inclusive, authentic, and emotional branding narrative. These findings emphasize that effective employer branding must be value-based and represent the real experiences of employees, not just aesthetic visualizations. The theoretical implications strengthen the relevance of Person–Organization Fit, Social Identity Theory, and Career Construction Theory in understanding the job selection process by Gen Z. Meanwhile, in practice, this study recommends that organizations develop participatory, reflective, and contextual employer branding strategies to the preferences of the younger generation. This study also opens up space for further studies with a wider demographic and work sector coverage.